New onset geriatric epilepsy: a randomized study of gabapentin, lamotrigine, and carbamazepine - Rowan, A J; Ramsay, R E; Collins, J F; Pryor, F; Boardman, K D; Uthman, B M; Spitz, M; Frederick, T; Towne, A; Carter, G S; Marks, W; Felicetta, J; et al. (Neurology, 2005)
To determine the relative tolerability and efficacy of two newer antiepileptic drugs, lamotrigine (LTG) and gabapentin (GBP), as compared to carbamazepine (CBZ) in older patients with epilepsy. This was an 18-center, randomized, double-blind, double dummy, parallel study of 593 elderly subjects with newly diagnosed seizures. Patients were randomly assigned to one of three treatment groups: GBP 1,500 mg/day, LTG 150 mg/day, CBZ 600 mg/day. The primary outcome measure was retention in trial for 12 months. Mean age was 72 years. The most common etiology was cerebral infarction. Patients had multiple medical conditions and took an average of seven comedications. Mean plasma levels at 6 weeks were as follows: GBP 8.67 +/- 4.83 microg/mL, LTG 2.87 +/- 1.60 microg/mL, CBZ 6.79 +/- 2.92 microg/mL. They remained stable throughout the trial. Early terminations: LTG 44.2%, GBP 51%, CBZ 64.5% (p = 0.0002). Significant paired comparisons: LTG vs CBZ: p < 0.0001; GBP vs CBZ: p = 0.008. Terminations for adverse events: LTG 12.1%, GBP 21.6%, CBZ 31% (p = 0.001). Significant paired comparisons: LTG vs CBZ: p < 0.0001; LTG vs GBP: p = 0.015. There were no significant differences in seizure free rate at 12 months. The main limiting factor in patient retention was adverse drug reactions. Patients taking lamotrigine (LTG) or gabapentin (GBP) did better than those taking carbamazepine. Seizure control was similar among groups. LTG and GBP should be considered as initial therapy for older patients with newly diagnosed seizures.